Democracia alimentar para populações em vulnerabilidade social: o caso de cozinhas solidárias em Manaus, Amazonas - Camila Lago Braga; Cristiane Cavalcante Lima (Confins)
Following the COVID-19 pandemic, there has been a significant increase in collaboration between various public, private and civil organizations. These initiatives include solidarity kitchens, which are based on the principle of the Human Right to Adequate Food. Therefore, the objective of this article is to analyse how Solidarity Kitchens (SKs) contribute to the construction of a food democracy, which considers food from the perspective of equal, free, sustainable access, and with society's participation in democratic decision-making. For this study, two SKs located in the municipality of Manaus, state of Amazonas, were selected. The research adopted a qualitative approach, using semi-structured interviews as the method of data collection. The results revealed the potential of SKs in Manaus to promote food democracy. Particularly noteworthy is the diversity of the served public and the fact that the service is provided by individuals involved in activism and familiar with the reality of the served communities.